Changes in mosquito species and blood meal composition associated with adulticide applications - Dongmin Kim; Nathan D. Burkett-Cadena; Lawrence E. Reeves (Scientific Reports, 2023)
Abstract Although adulticide application is a pillar in the integrated management of nuisance and vector mosquitoes, non-target effects of adulticide applications within ecosystems are a substantial concern. However, the impacts of adulticide applications on non-target organisms are not necessarily detrimental, and in some cases, may provide benefits to certain organisms or wildlife. Here, we hypothesized that adulticide applications have beneficial non-target impacts on vertebrate wildlife through reduced biting pressure. To test this, we collected mosquitoes from ultra-low volume Permanone-treated (intervention) and untreated (reference) areas and assessed mosquito abundance and diversity, and abundance of blood-engorged female mosquitoes. We performed DNA barcoding analysis on mosquito blood meals to identify host species. Our results demonstrated a significant reduction in mosquito abundance by 58.9% in the intervention areas, taking into account the reduction in reference areas. Consequently, this decline led to a 64.5% reduction in the abundance of blood-engorged females. We also found a temporal dynamic of mosquito composition driven by mosquito control actions in which different mosquito species became dominant at treated sites while composition at reference areas remained similar during the same period. The present study suggests that the beneficial effects of mosquito control treatments for humans extend to other vertebrates, which represents an unstudied and rarely recognized non-target impact.